Secondary modified zirconia powder and modification method thereof, 3D printing slurry and preparation method thereof

By secondary modification of zirconia powder, the problem of difficulty in creating complex structures and short storage period of photocured ceramic slurries in traditional molding processes is solved, and a low viscosity and high solids content of 3D printing slurries are prepared, which significantly improves oxidation The yield and mechanical properties of zirconium ceramic components.

CN119263822APending Publication Date: 2025-01-07AIDITE (QINHUANGDAO) TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411513909.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

It is difficult to manufacture zirconia ceramic components with complex structures in traditional molding processes, and the storage period of photocured ceramic slurry is short and the mechanical properties of finished parts are poor, which limits the application of zirconia materials in the field of photocuring molding.

Method used

By secondary modification of the zirconia powder, it improves its solubility and dispersion uniformity in the resin liquid, and a low viscosity and high solids content 3D printing slurry is prepared to extend the storage cycle and improve mechanical properties.

Benefits of technology

The low viscosity, long storage cycle and high mechanical properties of 3D printed slurries are achieved, which significantly improves the yield and application prospects of zirconia ceramic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses secondary modified zirconia powder and a modification method thereof, 3D printing slurry and a preparation method thereof, and belongs to the technical field of 3D printing materials. The secondary modified zirconium oxide powder is in an irregular shape, a spherical shape or a nearly spherical shape; the secondary modified zirconium oxide powder comprises the following components in parts by weight: 200 parts of zirconium oxide powder, 0.5-5 parts of a modifier, 150-200 parts of absolute ethyl alcohol, 0.1-1 part of a thermal curing agent and 0.5-5 parts of photosensitive resin; according to the preparation method, the zirconium oxide powder is subjected to primary modification by adopting the modifier, so that the hydrophilic and oleophylic characteristics of the zirconium oxide powder are changed, and the solubility of the zirconium oxide powder in resin liquid is increased; the zirconium oxide powder subjected to primary modification is subjected to secondary modification through the photosensitive resin in a thermocuring mode, the dispersion uniformity of the zirconium oxide powder in the photosensitive resin is improved, and the prepared 3D printing slurry has the advantages of being high in solid content, low in viscosity and long in storage time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of 3D printing materials, and in particular relates to a secondary modified zirconia powder and a modification method thereof, a 3D printing slurry and a preparation method thereof. Background Art

[0002] For the manufacture of some zirconia ceramic parts with complex geometric shapes and internal interconnected structures, traditional molding methods have certain limitations. At the same time, the design and manufacture of molded parts increase the manufacturing cost and preparation cycle of the products. In addition, defects such as edge cracking, wear, and surface damage are prone to occur during the processing, resulting in a low processing yield, which greatly limits the promotion and application of zirconia ceramic components. At present, with the improvement of people's living standards and the advancement of science and technology, people have higher and higher requirements for the appearance of products, and the scope of application of traditional molding processes has gradually narrowed. The emergence of light-curing additive manufacturing technology provides new possibilities and challenges for solving the problem of difficult processing of zirconia ceramic components, and opens up a new development direction for the preparation of personalized zirconia ceramic components with complex structures.

[0003] In recent years, the photocuring additive manufacturing technology has not only made it possible to demold zirconia ceramic components, but also overcome the shortcomings of traditional molding processes that make it difficult to manufacture complex components, so it has a wide range of application prospects. At present, the key issues limiting the prospects of zirconia materials in the field of photocuring molding are the short storage period of the slurry and the poor mechanical properties of the finished parts.

[0004] Patent CN 115043658 A discloses a method for preparing a photocurable ceramic slurry, which modifies the surface of ceramic powders by a modifier, so that the ceramic powders have a certain affinity with the resin, and effectively reduces the viscosity of the slurry by using a suitable dispersant, thereby obtaining a ceramic slurry with a high solid content. However, small molecules such as silane coupling agents or small molecule carboxylic acids are difficult to effectively reduce the viscosity in high-solid content zirconium oxide photosensitive slurries due to their short molecular chains, and the slurry prepared from zirconium oxide powder pre-modified by the dispersant is difficult to overcome the phenomenon of slurry bottom agglomeration caused by long-term storage. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a secondary modified zirconia powder and a modification method thereof, a 3D printing slurry and a preparation method thereof. The present invention improves the solubility of the zirconia powder in the resin liquid by performing secondary modification on the zirconia powder, and then adds the secondary modified zirconia powder to the 3D printing slurry, which effectively reduces the viscosity of the 3D printing slurry, prolongs the storage period, and improves the solid content and mechanical properties.

[0006] In a first aspect, the present invention provides a secondary modified zirconia powder, wherein the secondary modified zirconia powder comprises the following components in parts by weight: Zirconia powder 200 parts Modifier 0.5~5 parts 150~200 parts of anhydrous ethanol Thermal curing agent 0.1~1 part 0.5~5 parts of photosensitive resin.

[0007] Preferably, the secondary modified zirconia powder is in an irregular shape, a spherical shape or a nearly spherical shape.

[0008] Preferably, the secondary modified zirconia powder includes one of 3 mol yttrium-stabilized zirconia, 4 mol yttrium-stabilized zirconia, and 5 mol yttrium-stabilized zirconia.

[0009] Preferably, the average particle size D of the secondary modified zirconia powder is 50 It is 100~184nm.

[0010] After secondary modification, the hydrophilic and lipophilic properties of the zirconia powder can be changed. The obtained secondary modified zirconia powder can be more easily mixed with the resin liquid, thereby improving the solubility of the zirconia powder and the resin liquid and strengthening the suspension stability of the slurry.

[0011] In a second aspect, the present invention also provides a method for preparing a secondary modified zirconium oxide powder, comprising the following steps: Primary modification of zirconium oxide powder: anhydrous ethanol and a modifier are mixed in a certain proportion to prepare a solvent 1, and then zirconium oxide powder is added to obtain a mixed solution 1, and the mixed solution 1 is subjected to ball milling and stirring. After the ball milling is completed, the uniformly mixed mixed solution 1 is dried; after drying, the mixed solution 1 is ground and sieved to obtain primary modified zirconium oxide powder.

[0012] Specifically, 200 g of zirconium oxide powder can be added to solvent 1. For those skilled in the art, it is a conventional technique to select an appropriate amount of zirconium oxide powder according to the volume of the ball mill.

[0013] Preferably, in step (1), the volume ratio of anhydrous ethanol to the modifier is 100:(1-2).

[0014] Preferably, when the mixed solution 1 is ball-milled in step (1), the mixed solution 1 is placed on a ball mill for ball-milling and stirring.

[0015] Preferably, the ball milling time in step (1) is 4 to 6 h, for example, the ball milling time can be 4 h, 5 h, or 6 h.

[0016] Preferably, in step (1), the rotation speed of the ball mill is 600-800 r / min, and the ball-to-material ratio is 1:3. For example, the rotation speed of the ball mill can be 600 r / min, 700 r / min, or 800 r / min.

[0017] Preferably, when drying the mixed solution 1 in step (1), the mixed solution 1 can be placed in a blast drying oven for drying, and the temperature is set to 60°C.

[0018] Preferably, after the mixed solution in step (1) is dried, it is ground using a mortar and then sieved using a 100-mesh sieve to obtain a primary modified zirconium oxide powder.

[0019] Secondary modification of zirconium oxide: Anhydrous ethanol and photosensitive resin are mixed in a certain proportion to prepare solvent 2, and then primary modified zirconium oxide powder and thermal curing agent are added to obtain mixed solution 2, and the mixed solution 2 is ball-milled, stirred, dried, ground and sieved to obtain secondary modified zirconium oxide powder.

[0020] Specifically, 200 g of primary modified zirconium oxide powder can be added to solvent 2. For those skilled in the art, it is a conventional technique to select an appropriate amount of zirconium oxide powder according to the capacity of the ball mill.

[0021] Preferably, in step (2), the volume ratio of anhydrous ethanol to photosensitive resin is 100:(1-2).

[0022] Preferably, the modifier is one or more of KH570, methacrylic acid, stearic acid, vinyltriethoxysilane, and vinyltrimethoxysilane.

[0023] Preferably, the photosensitive resin is one or more of isobornyl methacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, cyclic trimethylolpropane formal acrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate, tricyclodecane dimethanol diacrylate, hydroxyethyl methacrylate, and di-trimethylolpropane tetraacrylate.

[0024] Preferably, the thermosetting agent is 0.1-1wt% of the primary modified zirconium oxide powder, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0025] Preferably, the thermal curing agent is one or more of cumene hydroperoxide, cumene hydroperoxide, dibenzoyl peroxide, tert-butyl hydroperoxide, tert-butyl peroxy-2-ethylhexanoate, and tert-butyl perbenzoate.

[0026] Preferably, when the mixed solution 2 is ball-milled in step (2), the mixed solution 2 is placed on a ball mill for ball-milling and stirring.

[0027] Preferably, in step (2), the mixed solution 2 is ball-milled and stirred by a ball mill, and the ball-milling time is 4 to 6 hours. For example, the ball-milling time can be 4 hours, 5 hours, or 6 hours.

[0028] Preferably, in step (2), the rotation speed of the ball mill is 600-800 r / min, and the ball-to-material ratio is 1:3. For example, the rotation speed of the ball mill can be 600 r / min, 700 r / min, or 800 r / min.

[0029] Preferably, when drying the mixed solution 2 in step (2), the mixed solution 2 can be placed in a blast drying oven for drying, and the temperature is set to 80°C.

[0030] Preferably, after the mixed solution 2 in step (2) is dried, it is ground using a mortar and then sieved using a 100-mesh sieve to obtain secondary modified zirconium oxide powder.

[0031] In a third aspect, the present invention further provides a 3D printing slurry, comprising the following components by mass fraction: Secondary modified zirconia powder 68~88% Oligomer 3~7% Organic monomer 2~6% Photoinitiator 1.5~4% Dispersant 0.5~25% Defoaming agent 0.05~0.2%.

[0032] In a fourth aspect, the present invention further provides a method for preparing a 3D printing slurry, comprising the following steps: (1) preparing a resin liquid, mixing an oligomer, an organic monomer, a photoinitiator, a dispersant and a defoamer, stirring the mixture with an electric stirrer, and fully dissolving the mixture to obtain a resin liquid; (2) preparing 3D printing slurry, adding the secondary modified zirconia powder into the resin liquid in batches and stirring and ball milling to obtain zirconia slurry;

[0033] In order to improve the mixing effect, each time the secondary modified zirconia powder is added, 10g, 20g or 30g of the secondary modified zirconia powder can be added at a time until the addition is complete. And after each addition, stir with an electric stirrer.

[0034] (3) Vacuum defoaming: defoam the zirconia slurry to eliminate the bubbles in the zirconia slurry.

[0035] Preferably, the oligomer is one or more of aliphatic polyurethane acrylate, polyether acrylate, epoxy acrylate resin, diphenylmethane diisocyanate, and m-xylylene diisocyanate.

[0036] Preferably, the dispersant is one or more of BYK-110, BYK-103, BYK-118, BYK-162, BYK-167, and BYK-2030.

[0037] Preferably, the defoaming agent is one or more of BYK-073, BYK-077, BYK-8800, and BYK-A 501.

[0038] Preferably, the organic monomer is one or more of isobornyl methacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, cyclic trimethylolpropane formal acrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate, tricyclodecane dimethanol diacrylate, hydroxyethyl methacrylate, and di-trimethylolpropane tetraacrylate.

[0039] Preferably, the photoinitiator is one or more of camphorquinone and tertiary amine co-initiator, bis(1-(2,4-difluorophenyl)-3-pyrrolyl)titanocene, N-alkylthioacridone, phenylethynyl dinitrophenol, 2,2-bis(o-chlorophenyl)-4,4,5,5-tetraphenyl-1,1-bisimidazole, 2,2,4-tris(2-chlorophenyl)-5-(3,4-dimethoxyphenyl)4,5-diphenyl-1,1-bisimidazole, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzoin diethyl ether, 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyl oxime).

[0040] Preferably, the speed of the electric stirrer in step (1) is 800-1400 r / min, for example, 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min, 1400 r / min. However, the speed is not limited to the values ​​listed, and other values ​​not listed in the range are also applicable.

[0041] Preferably, the stirring time of the electric stirrer in step (1) is 6 to 10 hours. For example, it can be 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours. However, it is not limited to the values ​​listed, and other values ​​not listed within the range are also applicable.

[0042] Preferably, the ball milling speed in step (2) is 600-1000 r / min. For example, it can be 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min, 1400 r / min. However, it is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0043] Preferably, the ball milling time in step (2) is 12 to 24 hours, for example, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, and 24 hours. During the ball milling process, the ball-to-material ratio is 1:5. However, the above values ​​are not limited to those listed, and other values ​​not listed in the range are also applicable.

[0044] Preferably, in step (3), a vacuum degassing machine is used for degassing, the vacuum degree is 0.1 mbar, and the air pump flow rate is 20-40 m 3 / h.

[0045] Preferably, when a vacuum degassing machine is used for degassing, the degassing time is 3 to 5 hours. For example, it can be 3 hours, 4 hours, or 5 hours. However, it is not limited to the values ​​listed, and other values ​​not listed within the range are also applicable.

[0046] Preferably, after obtaining the 3D printing slurry, the 3D printing slurry needs to be stored in a light-shielding bottle.

[0047] Those skilled in the art will appreciate that when printing with 3D printing slurry, an appropriate amount of 3D printing slurry can be taken according to actual printing requirements, and the performance of unused 3D printing slurry will not be affected. With the 3D printing slurry, printing can be performed with a printer to obtain a printed product.

[0048] Specifically, when printing a product by using a printer and 3D printing slurry, the following steps are included: Green body molding: According to the proportion of each component in the 3D printing slurry, the molding parameters of the printer are adjusted adaptively, such as the molding thickness can be set to 25~45μm, the bottom exposure time can be set between 15~25s, and the light intensity can be set to 35~58mW / cm 2 , the light energy is set at 130~350mJ / cm 2. . The formed green body is obtained by printing and 3D printing the slurry.

[0049] It should be noted that before the printer is run, the printer is calibrated, debugged and leveled to ensure that all molded samples are in the same manufacturing plane, which is known to those skilled in the art.

[0050] Disassembly and cleaning of the blank: After printing, use a special tool to disassemble the printed sample without damaging the printing substrate of the printer. Clean the surface of the sample with cleaning fluid or alcohol to remove excess support. In order to prevent the residual cleaning fluid or alcohol from corroding the sample, it is necessary to blow off the cleaning fluid remaining on the surface of the sample with a spray gun after cleaning.

[0051] Degreasing of green body: In order to obtain dense samples, it is necessary to burn off the organic matter in the green body, such as polymer photosensitive resin, photoinitiator and dispersant, which is called degreasing.

[0052] The degreasing procedure is as follows: increase the temperature from room temperature to 250°C at a heating rate of 1°C / min, and keep warm for 2 hours; increase the temperature from 250°C to 550°C at a heating rate of 0.5°C / min, and keep warm for 3 hours; increase the temperature from 550°C to 800°C at a heating rate of 2°C / min, and keep warm for 1 hour; increase the temperature from 800°C to 1000°C at a heating rate of 4°C / min, and keep warm for 2 hours; cool to room temperature with the furnace. The entire degreasing process is completed in an air atmosphere.

[0053] (4) Sintering: The degreased green body is sintered in an air atmosphere. The sintering curve is as follows: heating from 25°C to 1200°C at a heating rate of 7.5°C / min, keeping at that temperature for 1 hour; heating from 1200°C to 1600°C at a heating rate of 4°C / min, keeping at that temperature for 2 hours; and cooling to room temperature in the furnace.

[0054] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses a modifier to modify zirconium oxide powder once, thereby changing the hydrophilic and lipophilic properties of the zirconium oxide powder and increasing the solubility of the zirconium oxide powder in the resin liquid. The zirconium oxide powder after the primary modification is modified by heat curing the photosensitive resin for a secondary modification, thereby improving the dispersion uniformity of the zirconium oxide powder in the photosensitive resin, so that the prepared 3D printing slurry has the advantages of high solid content, low viscosity and long storage time. DETAILED DESCRIPTION

[0055] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] ①Prepare primary modified zirconia powder.

[0057] Preparation of primary modified zirconium oxide powder

[0058] Weigh 150 parts of anhydrous ethanol and 1.5 parts of modifier KH570, mix anhydrous ethanol and KH570 evenly, and configure them into solvent one. Then add 200 parts of zirconium oxide powder to solvent one to obtain mixed solution one, put the mixed solution one on a ball mill for ball milling and stirring, the stirring time is 4h, the speed is 600r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. Put the mixed mixed solution one into a blast drying oven for drying to obtain a first modified zirconium oxide block one. Put the first modified zirconium oxide block one into a mortar and grind it, then pass it through a 100-mesh sieve to obtain a first modified zirconium oxide powder one.

[0059] Preparation of primary modified zirconium oxide powder

[0060] Weigh 160 parts of anhydrous ethanol and 1.6 parts of modifier KH570, mix anhydrous ethanol and KH570 evenly, and configure them into solvent 2. Then add 200 parts of zirconium oxide powder to solvent 2 to obtain mixed solution 2, put mixed solution 2 on a ball mill for ball milling and stirring, the stirring time is 4.5h, the speed is 600r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. Put the mixed solution 2 after mixing evenly into a blast drying oven for drying to obtain a first modified zirconium oxide block 2. Put the first modified zirconium oxide block 2 into a mortar and grind it, then pass it through a 100-mesh sieve to obtain a first modified zirconium oxide powder 2.

[0061] Preparation of primary modified zirconium oxide powder

[0062] Take 170 parts of anhydrous ethanol and 1.7 parts of modifier KH570, mix anhydrous ethanol and KH570 evenly, and configure them into solvent three. Then add 200 parts of zirconium oxide powder to solvent three to obtain mixed solution three, put mixed solution three on a ball mill for ball milling and stirring, the stirring time is 5h, the speed is 700r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. Put the mixed solution three after mixing evenly into a blast drying oven for drying to obtain a first modified zirconium oxide block three. Put the first modified zirconium oxide block three into a mortar and grind it, then pass it through a 100-mesh sieve to obtain a first modified zirconium oxide powder three.

[0063] Preparation of primary modified zirconium oxide powder

[0064] Take 175 parts of anhydrous ethanol and 1.75 parts of modifier KH570, mix the anhydrous ethanol and KH570 evenly, and configure them into solvent 4. Then add 200 parts of zirconium oxide powder to solvent 4 to obtain mixed solution 4, put the mixed solution 4 on a ball mill for ball milling and stirring, the stirring time is 5h, the speed is 700r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. The mixed mixed solution 4 is placed in a blast drying oven for drying to obtain a first modified zirconium oxide block 4. After the first modified zirconium oxide block 4 is ground in a mortar, it is passed through a 100-mesh sieve to obtain a first modified zirconium oxide powder 4.

[0065] Preparation of one-time modified zirconium oxide powder

[0066] Take 180 parts of anhydrous ethanol and 1.8 parts of modifier KH570, mix anhydrous ethanol and KH570 evenly, and configure them into solvent five. Then add 200 parts of zirconium oxide powder to solvent five to obtain mixed solution five, put mixed solution five on a ball mill for ball milling and stirring, the stirring time is 5.5h, the speed is 750r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. Put the mixed solution five after mixing evenly into a blast drying oven for drying to obtain a first modified zirconium oxide block five. Put the first modified zirconium oxide block five into a mortar and grind it, then pass it through a 100-mesh sieve to obtain a first modified zirconium oxide powder five.

[0067] Preparation of one-time modified zirconium oxide powder

[0068] Take 190 parts of anhydrous ethanol and 1.9 parts of modifier KH570, mix anhydrous ethanol and KH570 evenly, and configure them into solvent 6. Then add 200 parts of zirconium oxide powder to solvent 6 to obtain mixed solution 6, put the mixed solution 6 on a ball mill for ball milling and stirring, the stirring time is 6h, the speed is 800r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. Put the mixed mixed solution 6 into a blast drying oven for drying to obtain a first modified zirconium oxide block 6. Put the first modified zirconium oxide block 6 into a mortar and grind it, then pass it through a 100-mesh sieve to obtain a first modified zirconium oxide powder 6.

[0069] Preparation of primary modified zirconium oxide powder

[0070] Take 195 parts of anhydrous ethanol and 1.95 parts of modifier KH570, mix anhydrous ethanol and KH570 evenly, and configure them into solvent seven. Then add 200 parts of zirconium oxide powder to solvent seven to obtain mixed solution seven, put mixed solution seven on a ball mill for ball milling stirring, the stirring time is 4h, the speed is 700r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. The mixed mixed solution seven is placed in a blast drying oven for drying to obtain a first modified zirconium oxide block seven. After the first modified zirconium oxide block seven is put into a mortar and ground, it is passed through a 100-mesh sieve to obtain a first modified zirconium oxide powder seven.

[0071] Preparation of primary modified zirconium oxide powder

[0072] Take 200 parts of anhydrous ethanol and 2 parts of modifier KH570, mix the anhydrous ethanol and KH570 evenly, and configure them into solvent eight. Then add 200 parts of zirconium oxide powder to solvent eight to obtain mixed solution eight, put the mixed solution eight on a ball mill for ball milling and stirring, the stirring time is 4h, the speed is 700r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. Put the mixed solution eight into a blast drying oven for drying to obtain a first modified zirconium oxide block eight. Put the first modified zirconium oxide block eight into a mortar and grind it, then pass it through a 100-mesh sieve to obtain a first modified zirconium oxide powder eight.

[0073] It should be noted that in the process of preparing the primary modified zirconium oxide powder, the number of parts of a certain component is equal to the mass of the component, in grams. For example, 200 parts of zirconium oxide powder is 200 grams of zirconium oxide powder, and 180 parts of anhydrous ethanol is 180 grams of anhydrous ethanol. In addition, the solvent 1, solvent 2...solvent 8 mentioned above are only for the purpose of distinguishing each solvent, and similarly, the mixed solution 1, mixed solution 2, etc. are the same.

[0074] ②Prepare secondary modified zirconia powder.

[0075] Preparation of secondary modified zirconia powder

[0076] Take 170 parts of anhydrous ethanol and 1.7 parts of 1,6-hexanediol diacrylate, mix the anhydrous ethanol and 1,6-hexanediol diacrylate evenly, and configure them into solvent one. Then add 200 parts of primary modified zirconium oxide powder three and 0.1 parts of thermal curing agent hydroperoxide isopropylbenzene to solvent one to obtain a mixed solution one, and place the mixed solution one on a ball mill for ball milling and stirring, the stirring time is 5h, the speed is 700r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. The mixed solution one after mixing is placed in a blast drying oven for drying to obtain a secondary modified zirconium oxide block one. After the secondary modified zirconium oxide block one is ground in a mortar, it is passed through a 100-mesh sieve to obtain a secondary modified zirconium oxide powder one.

[0077] Preparation of secondary modified zirconia powder

[0078] Take 175 parts of anhydrous ethanol and 1.75 parts of 1,6-hexanediol diacrylate, mix anhydrous ethanol and 1,6-hexanediol diacrylate evenly, and configure them into solvent 2. Then add 200 parts of primary modified zirconium oxide powder 4 and 0.1 parts of thermosetting agent cumene hydroperoxide to solvent 2 to obtain mixed solution 2, and place mixed solution 2 on a ball mill for ball milling and stirring, the stirring time is 5h, the speed is 700r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. The mixed solution 2 after mixing is placed in a blast drying oven for drying to obtain a secondary modified zirconium oxide block 2. After the secondary modified zirconium oxide block 2 is ground in a mortar, it is passed through a 100-mesh sieve to obtain a secondary zirconium oxide powder 2.

[0079] Preparation of secondary modified zirconia powder

[0080] Take 180 parts of anhydrous ethanol and 1.8 parts of 1,6-hexanediol diacrylate, mix the anhydrous ethanol and 1,6-hexanediol diacrylate evenly, and configure them into solvent three. Then add 200 parts of primary modified zirconium oxide powder five and 0.1 parts of thermosetting agent cumene hydroperoxide to solvent three to obtain mixed solution three, put mixed solution three on a ball mill for ball milling and stirring, the stirring time is 5.5h, the speed is 750r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. The mixed solution three after mixing is placed in a blast drying oven for drying to obtain a secondary modified zirconium oxide block three. After the secondary modified zirconium oxide block three is ground in a mortar, it is passed through a 100-mesh sieve to obtain a secondary zirconium oxide powder three.

[0081] Preparation of secondary modified zirconia powder Take 190 parts of anhydrous ethanol and 1.9 parts of 1,6-hexanediol diacrylate, mix the anhydrous ethanol and 1,6-hexanediol diacrylate evenly, and configure them into solvent 4. Then add 200 parts of primary modified zirconium oxide powder 6 and 0.1 parts of thermal curing agent cumene hydroperoxide to solvent 4 to obtain mixed solution 4, put the mixed solution 4 on a ball mill for ball milling and stirring, the stirring time is 6h, the speed is 800r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. The mixed solution 6 after mixing is placed in a blast drying oven for drying to obtain a secondary modified zirconium oxide block 4. After the secondary modified zirconium oxide block 4 is ground in a mortar, it is passed through a 100-mesh sieve to obtain a secondary zirconium oxide powder 4.

[0082] Preparation of secondary modified zirconia powder

[0083] Take 195 parts of anhydrous ethanol and 1.95 parts of 1,6-hexanediol diacrylate, mix the anhydrous ethanol and 1,6-hexanediol diacrylate evenly, and configure them into solvent five. Then add 200 parts of primary modified zirconium oxide powder seven and 0.1 parts of thermal curing agent cumene hydroperoxide to solvent seven to obtain mixed solution five, put the mixed solution five on a ball mill for ball milling and stirring, the stirring time is 4h, the speed is 700r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. Put the mixed solution five after mixing evenly into a blast drying oven for drying to obtain a secondary modified zirconium oxide block five. Put the secondary modified zirconium oxide block five into a mortar and grind it, then pass it through a 100-mesh sieve to obtain secondary zirconium oxide powder five.

[0084] Preparation of secondary modified zirconia powder

[0085] Take 200 parts of anhydrous ethanol and 2 parts of 1,6-hexanediol diacrylate, mix the anhydrous ethanol and 1,6-hexanediol diacrylate evenly, and configure them into solvent 6. Then add 200 parts of primary modified zirconium oxide powder 8 and 0.1 parts of thermal curing agent cumene hydroperoxide to solvent 6 to obtain mixed solution 6, put the mixed solution 6 on a ball mill for ball milling and stirring, the stirring time is 4h, the speed is 700r / min, the ball-to-material ratio is 1:3, and the mixture is evenly mixed. Put the mixed solution 6 into a blast drying oven for drying to obtain a secondary modified zirconium oxide block 6. Put the secondary modified zirconium oxide block 6 into a mortar and grind it, then pass it through a 100-mesh sieve to obtain secondary zirconium oxide powder 6.

[0086] It should be noted that in the process of preparing the secondary modified zirconia powder, the number of parts of a certain component is equal to the mass of the component, in grams. For example, 200 parts of zirconia powder is 200 grams of zirconia powder, and 180 parts of anhydrous ethanol is 180 grams of anhydrous ethanol. In addition, the above-mentioned solvent one, solvent two...solvent eight are only for the purpose of distinguishing each solvent. Similarly, the mixed liquid one, mixed liquid two, etc. are the same. In addition, in the process of preparing the secondary modified zirconia powder, the prepared solvent and mixed liquid are reconfigured separately, and the only difference between them and the solvent and mixed liquid used to prepare the primary modified zirconia powder is the composition, rather than the same solvent or mixed liquid being reused.

[0087] Prepare 3D printing slurry.

[0088] In the process of preparing 3D printing slurry in Example 1-Example 6 and Comparative Example 1-Comparative Example 2, the components are as shown in Table 1.

[0089] Table 1: Detailed list of components of 3D printing slurry

[0090] In Table 1, the content of each component is calculated by mass fraction, the unit is %, and the total mass fraction of each component is 100%.

[0091] When preparing the 3D printing slurry in Examples 1 to 6 and Comparative Examples 1 to 2, it is first necessary to prepare a resin liquid, the resin liquid components include oligomers, organic monomers, photoinitiators, dispersants and defoamers. In Examples 1 to 6 and Comparative Examples 1 to 2, the oligomer is aliphatic polyurethane acrylate, the organic monomer is 1,6-hexanediol diacrylate, the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, the dispersant is BYK-103, and the defoamer is BYK-8800.

[0092] In Example 1, after mixing the components outside the powder according to Table 1, stir with an electric stirrer at a speed of 800r / min for 10 hours until all components are fully dissolved to obtain a resin liquid. According to the mass fraction of the powder in Table 1, weigh the secondary modified zirconia powder one, and add the secondary modified zirconia powder one to the resin liquid in batches. Each time, it can be added in an amount of 20g, 30g, or 40g, which helps to fully mix. Stir with an electric stirrer after each addition, and ball milling is performed after all the powders have been added. During the ball milling process, the speed is 600r / min, the ball milling time is 24h, and the ball milling ratio is 1:5. After the ball milling is completed, the slurry is placed in a vacuum degassing machine for degassing, and the vacuum degree is set to 0.1mbar and the air pump flow rate is 20m 3 / h, degassing time 5h, until there are no obvious bubbles on the slurry surface, to obtain 3D printing slurry.

[0093] In Example 2, after mixing the components outside the powder according to Table 1, stir with an electric stirrer at a speed of 900r / min for 9 hours until all components are fully dissolved to obtain a resin liquid. According to the mass fraction of the powder in Table 1, weigh the secondary modified zirconia powder 2, and add the secondary modified zirconia powder 2 to the resin liquid in batches. Each time, it can be added in an amount of 20g, 30g, and 40g, which helps to fully mix. Stir with an electric stirrer after each addition, and ball milling is performed after all the powders have been added. During the ball milling process, the speed is 800r / min, the ball milling time is 15h, and the ball milling ratio is 1:5. After the ball milling is completed, the slurry is placed in a vacuum degassing machine for degassing, and the vacuum degree is set to 0.1mbar and the air pump flow rate is 30m 3 / h, degassing time 4h, until there are no obvious bubbles on the slurry surface, to obtain 3D printing slurry.

[0094] In Example 3, after mixing the components outside the powder according to Table 1, stir with an electric stirrer at a speed of 1000r / min for 8 hours until all components are fully dissolved to obtain a resin liquid. According to the mass fraction of the powder in Table 1, weigh the secondary modified zirconia powder three, and add the secondary modified zirconia powder three to the resin liquid in batches. Each time, 20g can be added, which helps to fully mix. Stir with an electric stirrer after each addition, and ball milling is performed after all the powders have been added. During the ball milling process, the speed is 800r / min, the ball milling time is 22h, and the ball milling ratio is 1:5. After the ball milling is completed, the slurry is placed in a vacuum degassing machine for degassing, and the vacuum degree is set to 0.1mbar and the air pump flow rate is 400m 3 / h, degassing time 3h, until there are no obvious bubbles on the slurry surface, to obtain 3D printing slurry.

[0095] In Example 4, after mixing the components outside the powder according to Table 1, stir with an electric stirrer at a speed of 1100r / min for 7 hours until all components are fully dissolved to obtain a resin liquid. According to the mass fraction of the powder in Table 1, weigh the secondary modified zirconia powder four, and add the secondary modified zirconia powder four to the resin liquid in batches. Each time, 20g can be added, which helps to fully mix. Stir with an electric stirrer after each addition, and ball milling is performed after all the powders have been added. During the ball milling process, the speed is 800r / min, the ball milling time is 22h, and the ball milling ratio is 1:5. After the ball milling is completed, the slurry is placed in a vacuum degassing machine for degassing, and the vacuum degree is set to 0.1mbar and the air pump flow rate is 20m 3 / h, degassing time 5h, until there are no obvious bubbles on the slurry surface, to obtain 3D printing slurry.

[0096] In Example 5, after mixing the components outside the powder according to Table 1, stir with an electric stirrer at a speed of 1200r / min for 6 hours until all components are fully dissolved to obtain a resin liquid. According to the mass fraction of the powder in Table 1, weigh the secondary modified zirconia powder five, and add the secondary modified zirconia powder five to the resin liquid in batches. Each time, 20g can be added, which helps to fully mix. Stir with an electric stirrer after each addition, and ball milling is performed after all the powders have been added. During the ball milling process, the speed is 700r / min, the ball milling time is 20h, and the ball milling ratio is 1:5. After the ball milling is completed, the slurry is placed in a vacuum degassing machine for degassing, and the vacuum degree is set to 0.1mbar and the air pump flow rate is 30m 3 / h, degassing time 4h, until there are no obvious bubbles on the slurry surface, to obtain 3D printing slurry.

[0097] In Example 6, after mixing the components outside the powder as shown in Table 1, stir with an electric stirrer at a speed of 1200r / min for 6 hours until all components are fully dissolved to obtain a resin liquid. According to the mass fraction of the powder in Table 1, weigh the secondary modified zirconia powder six, and add the secondary modified zirconia powder six to the resin liquid in batches. Each time, 20g can be added, which helps to fully mix. Stir with an electric stirrer after each addition, and ball milling is performed after all the powders have been added. During the ball milling process, the speed is 800r / min, the ball milling time is 22h, and the ball milling ratio is 1:5. After the ball milling is completed, the slurry is placed in a vacuum degassing machine for degassing, and the vacuum degree is set to 0.1mbar and the air pump flow rate is 30m 3 / h, degassing time 4h, until there are no obvious bubbles on the slurry surface, to obtain 3D printing slurry.

[0098] In Comparative Example 1, a 3D printing slurry was prepared, which was the same as that in Example 1 except that the powder added was different, and will not be described here.

[0099] In Comparative Example 2, a 3D printing slurry was prepared, which was the same as that in Example 2 except that the powder added was different, and will not be described here.

[0100] In Comparative Example 3, a 3D printing slurry was prepared, which was the same as that in Example 3 except for the different contents of powder and dispersant added, and will not be described here.

[0101] In Comparative Example 4, a 3D printing slurry was prepared, which was the same as that in Example 4 except for the different contents of powder and dispersant added, and will not be described here.

[0102] Prepare 3D printed samples.

[0103] Application Example 1

[0104] Light-curing 3D printing: Use a light-curing 3D printer with a light intensity of 35mW / cm 2 , under a light source of visible light with a wavelength of 420 nm, the 3D printing slurry prepared in Example 1 was 3D printed with a layer thickness of 25 μm and then exposed and cured for 10 seconds to obtain a molded body, i.e., a printed sample.

[0105] After printing, use a special tool to disassemble the printed sample without damaging the printed substrate, and use cleaning fluid or alcohol to remove the support and clean it. To prevent the residual cleaning fluid from corroding the sample, blow away the residual cleaning fluid with a spray gun after cleaning.

[0106] Degreasing of the blank: In order to obtain a dense printed sample, it is necessary to burn off the organic matter in the blank, such as polymer photosensitive resin, photoinitiator and dispersant, which is called degreasing.

[0107] The degreasing process is as follows: heating from room temperature to 250℃ at a heating rate of 1℃ / min, and keeping warm for 2h; heating from 250℃ to 550℃ at a heating rate of 0.5℃ / min, and keeping warm for 3h; heating from 550℃ to 800℃ at a heating rate of 2℃ / min, and keeping warm for 1h; heating from 800℃ to 1000℃ at a heating rate of 4℃ / min, and keeping warm for 2h; cooling to room temperature with the furnace. The entire degreasing process is completed in an air atmosphere.

[0108] Sintering: The degreased green body is sintered in air. The sintering curve is: heating from 25°C to 1200°C at a heating rate of 7.5°C / min, and keeping warm for 1h; heating from 1200°C to 1600°C at a heating rate of 4°C / min, and keeping warm for 2h; cooling to room temperature with the furnace. The final printed sample (zirconia ceramic product) is obtained.

[0109] Application Example 2

[0110] In the process of printing the printed sample (zirconia ceramic product) in Application Example 2, except for using the 3D printing slurry of Example 2, the rest is the same as that in Application Example 1, and will not be repeated here.

[0111] Application Example 3

[0112] In the process of printing the printed sample (zirconia ceramic product) in Application Example 3, except for using the 3D printing slurry of Example 3, the rest is the same as that in Application Example 1, and will not be repeated here.

[0113] Application Example 4

[0114] In the process of printing the printed sample (zirconia ceramic product) in Application Example 4, except for using the 3D printing slurry of Example 4, the rest is the same as that in Application Example 1, and will not be repeated here.

[0115] Application Example 5

[0116] In the process of printing the printed sample (zirconia ceramic product) in Application Example 5, except for using the 3D printing slurry of Example 5, the rest is the same as that in Application Example 1, and will not be repeated here.

[0117] Application Example 6

[0118] In the process of printing the printed sample (zirconia ceramic product) in Application Example 6, except for using the 3D printing slurry of Example 6, the rest is the same as that in Application Example 1, and will not be repeated here.

[0119] Application Comparative Example 1

[0120] In the process of printing the printed sample (zirconia ceramic product) in comparative application example 1, except for using the 3D printing slurry of comparative example 1, the rest is the same as that of application example 1, and will not be repeated here.

[0121] Application Comparative Example 2

[0122] In the process of printing the printed sample (zirconia ceramic product) in comparative application example 2, except for using the 3D printing slurry of comparative example 2, the rest is the same as that of application example 1, and will not be repeated here.

[0123] Application Comparative Example 3

[0124] In the process of printing the printed sample (zirconia ceramic product) in comparative application example 3, except for using the 3D printing slurry of comparative example 3, the rest is the same as that of application example 1, and will not be repeated here.

[0125] Application Comparative Example 4

[0126] In the process of printing the printed sample (zirconia ceramic product) in comparative application example 4, except for using the 3D printing slurry of comparative example 4, the rest is the same as that of application example 1, and will not be repeated here.

[0127] Performance Testing:.

[0128] The slurry viscosity is measured according to the experiment specified in ISO 19613:2018 (en) "Fine ceramics (advanced ceramics, advanced technical ceramics) — Measurement of viscosity of ceramic slurry by use of a rotational viscometer". The specific steps are as follows: 1.Material: Zirconia slurry.

[0129] 2. Apparatus: rotational viscometer, beaker, alcohol.

[0130] 3. Steps: 1) Prepare the liquid to be tested and place it in a beaker or straight container with a diameter of not less than 70 mm and a height of not less than 125 mm; 2) Check whether the level bubble of the instrument is centered, and adjust the three level adjustment screws on the base of the main unit to make the level bubble on the viscometer head in the center; 3) Refer to the range table, hang the appropriate rotor into the connector, turn it left to install, and turn it right to remove; 4) Slowly adjust the lifting knob to adjust the height of the rotor in the measured liquid until the liquid mark on the rotor (the middle of the groove) is level with the liquid surface; 5) Before measuring, first estimate the viscosity range of the liquid to be measured, and then select the appropriate rotor and speed in the range table; 6) After setting the relevant test parameters, press the OK button to start the measurement. When the vertical bar on the right side of the display rises from bottom to full scale, the viscosity value displayed on the screen is the measured value (at this time, you can press the RESET button to pause and record the measurement results).

[0131] Note: To ensure measurement accuracy, the range percentage reading should be controlled between 10% and 90% (close to 50% is best). The measurement needs to be repeated three times, and the final result is the average of the three measurements.

[0132] The Vickers hardness of the sample is measured according to the experiment specified in GB / T 16534-2009 "Test Method for Room Temperature Hardness of Fine Ceramics". The specific steps are as follows: 1.Material: Zirconia ceramic.

[0133] 2. Instrument: Vickers hardness tester (calibrated).

[0134] 3. Steps: 1) Prepare the ceramic sample to be tested. The sample thickness should be no less than 0.5 mm, should be at least 1.5 times the diagonal length of the indentation, and should be at least 2 times the crack length. During the entire test, there should be no visible indentation damage on the back of the sample; 2) The sample is placed on a rigid support. The support surface should be clean and free of foreign matter. The sample is placed firmly on the support to ensure that it will not move during the entire test process. 3) Make the indenter contact the surface of the sample and apply the test force perpendicular to the test surface. There should be no impact and vibration during the loading process until the test force is applied to the specified value. The maximum constant test force is maintained for 15 s. 4) Carefully adjust the lighting and focus to obtain a clear indentation image. The two tips of the indentation should be in focus at the same time. Do not change the focus condition when measuring the distance between the indentation tips. 5) Calculate the Vickers hardness (HV) of the effective indentation using the formula:

[0135] Where: F——test force, in Newton (N) d——arithmetic mean of two diagonals d1 and d2, in millimeters (mm) Note: To ensure measurement accuracy, the measurement needs to be repeated five times, and the final result is the average value of the five measurements.

[0136] The flexural strength of the sample was measured by a three-point bending test according to the test specified in GB 30367-2013 Dental Ceramic Materials. The specific steps are as follows: 1.Material: Zirconia ceramic.

[0137] 2. Apparatus: universal mechanical testing machine.

[0138] 3. Steps: 1) Prepare the ceramic sample to be tested. The sample size is width: 4.0 mm ± 0.2 mm; thickness: 3.0 mm ± 0.2 mm; chamfer: 0.09 mm ~ 0.15 mm; 2) Test the cross-sectional dimensions of each specimen with an accuracy of ±0.01 mm; 3) Place a specimen at the center of the support point of the testing machine so that the load is applied to the 4 mm wide surface of the specimen in a direction perpendicular to the long axis of the specimen; 4) Determine the load required for the specimen to break, with the data accurate to 0.1 N; 5) The crosshead speed of the testing machine is (1±0.5) mm / min, and the above steps are repeated to test the remaining samples; 6) Calculate the flexural strength using the Weibull formula in megapascals (MPa), and record the average and standard values ​​of the flexural strength:

[0139] Where: P——Breaking load, in Newton (N) L——test span (the distance between the centers of the two supporting cylinders), in millimeters (mm) w——The width of the specimen, the dimension of the side perpendicular to the load direction, in millimeters (mm) b——The thickness of the specimen, the dimension of the side parallel to the load direction, in millimeters (mm) Note: To ensure measurement accuracy, the number of samples to be tested is at least 10, and the final result is the average of ten measurements.

[0140] Corresponding to use case 1 to application case 6 and application comparison example 1 to application comparison example 2 were tested, and the test results are shown in Table 2.

[0141] Table 2: Performance test results

[0142] It can be seen from Table 2 that the ceramic powder used in the 3D printing slurry prepared by Application Comparative Example 1-Application Comparative Example 2 is a primary modified zirconia powder, and the ceramic powder used in the 3D printing slurry prepared by Application Example 1-Application Example 6 is a secondary modified zirconia powder. After testing the ceramics formed by the two slurries, it was found that the slurry viscosity measured by Application Comparative Example 1 was greater than the slurry viscosity of Application Example 1, and the slurry viscosity measured by Application Comparative Example 2 was much higher than the slurry viscosity of Application Example 6. The Vickers hardness and flexural strength of the ceramic in Application Comparative Example 1 were both lower than those in Application Example 1, and the Vickers hardness and flexural strength of the ceramic in Application Comparative Example 2 were both lower than those in Application Example 6. Therefore, the 3D printing slurry prepared by adding secondary modified zirconia powder has lower viscosity, higher Vickers hardness, higher flexural strength, and better powder solubility and suspension.

[0143] The ceramic powder used in the 3D printing slurry prepared in Application Examples 1-6 is secondary modified zirconia powder, and the amount of powder added gradually increases. After testing the 6 slurries and formed ceramic samples, it can be seen that with the increase in the amount of powder added, the viscosity of the slurry gradually increases, but it is maintained at a low level overall. When the maximum solid content is 88, the slurry viscosity is only 15350mPa·s, but the hardness and flexural strength of the ceramic sample increase significantly. When the maximum solid content is 88, the hardness and flexural strength of the ceramic sample are 1370.8HV and 1012.939MPa, respectively, which almost reaches the level of traditional molding technology. Therefore, the use of secondary modified zirconia powder can prepare high-solid content 3D printing slurry, and then form high-performance ceramics.

[0144] In the 3D printing slurry prepared by using comparative examples 3-4, the ceramic powder used is a secondary modified zirconia powder, but the solid content of comparative example 3 is too low, and the solid content of comparative example 4 is too high. It can be seen from the performance test results that neither too low nor too high solid content can significantly improve the performance. Among them, although comparative example 4 prepared a slurry with a high solid content, the slurry viscosity was too high and molding was difficult, so the performance was reduced.

[0145] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A secondary modified zirconium oxide powder, characterized in that: The secondary modified zirconia powder is in an irregular shape, a spherical shape or a nearly spherical shape; the secondary modified zirconia powder comprises the following components in parts by weight: Zirconia powder 200 parts Modifier 0.5~5 parts 150~200 parts of anhydrous ethanol Thermal curing agent 0.1~1 part 0.5~5 parts of photosensitive resin.

2. The method for preparing a secondary modified zirconium oxide powder according to claim 1, characterized in that: The following steps are involved: (1) Primary modification of zirconium oxide powder: anhydrous ethanol and a modifier are mixed in a certain proportion to prepare a solvent 1, and then zirconium oxide powder is added to obtain a mixed solution 1, and the mixed solution 1 is ball-milled, stirred, dried, ground and sieved to obtain a primary modified zirconium oxide powder; (2) Secondary modification of zirconium oxide: Anhydrous ethanol and photosensitive resin are mixed in a certain proportion to prepare solvent 2, and then primary modified zirconium oxide powder and a thermal curing agent are added to obtain mixed solution 2. The mixed solution 2 is ball-milled, stirred, dried, ground and sieved to obtain secondary modified zirconium oxide powder.

3. The method for preparing a secondary modified zirconium oxide powder according to claim 2, characterized in that: In step (1), the volume ratio of anhydrous ethanol to the modifier is 100:(1~2), and in step (2), the volume ratio of anhydrous ethanol to the photosensitive resin is 100:(1~2).

4. The method for preparing a secondary modified zirconium oxide powder according to claim 2, characterized in that: The modifier is one or more of KH570, methacrylic acid, stearic acid, vinyl triethoxy silane and vinyl trimethoxy silane.

5. The method for preparing a secondary modified zirconium oxide powder according to claim 2, characterized in that: The photosensitive resin is one or more of isobornyl methacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, cyclic trimethylolpropane formal acrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate, tricyclodecane dimethanol diacrylate, hydroxyethyl methacrylate, and di-trimethylolpropane tetraacrylate.

6. The method for preparing a secondary modified zirconium oxide powder according to claim 2, characterized in that: In terms of weight percentage, the thermal curing agent is 0.1-1wt% of the primary modified zirconium oxide powder, and the thermal curing agent is one or more of cumene hydroperoxide, cumene hydroperoxide, dibenzoyl peroxide, tert-butyl hydroperoxide, tert-butyl peroxy-2-ethylhexanoate, and tert-butyl perbenzoate.

7. The method for preparing a secondary modified zirconium oxide powder according to claim 2, characterized in that: In step (1) and step (2), the ball milling time is 4 to 6 hours; the rotation speed is 600 to 800 r / min, and the ball-to-material ratio is 1:

3.

8. Use of the secondary modified zirconia powder as claimed in claim 1 or the secondary modified zirconia powder prepared by the preparation method of the secondary modified zirconia powder as claimed in claims 2 to 8 in 3D printing slurry.

9. A 3D printing slurry, characterized in that: According to mass fraction, it includes the following components: Secondary modified zirconia powder 68~88% Oligomer 3~7% Organic monomer 2~6% Photoinitiator 1.5~4% Dispersant 0.5~25% Defoaming agent 0.05~0.2%.

10. The method for preparing a 3D printing slurry according to claim 9, characterized in that: The following steps are involved: (1) preparing a resin liquid, mixing an oligomer, an organic monomer, a photoinitiator, a dispersant and a defoamer, stirring the mixture with an electric stirrer, and fully dissolving the mixture to obtain a resin liquid; (2) preparing 3D printing slurry, adding the secondary modified zirconia powder into the resin liquid in batches and performing ball milling and stirring to obtain zirconia slurry; (3) Vacuum defoaming: defoam the zirconia slurry to eliminate the bubbles in the zirconia slurry.

11. The method for preparing a 3D printing slurry according to claim 10, characterized in that: The oligomer is one or more of aliphatic polyurethane acrylate, polyether acrylate, epoxy acrylate resin, diphenylmethane diisocyanate, and meta-xylylene diisocyanate.

12. The method for preparing a 3D printing slurry according to claim 10, characterized in that: In step (1), the dispersant is one or more of BYK-110, BYK-103, BYK-118, BYK-162, BYK-167, and BYK-2030.

13. The method for preparing a 3D printing slurry according to claim 10, characterized in that: In step (1), the defoaming agent is one or more of BYK-073, BYK-077, BYK-8800, and BYK-A 501.

14. The method for preparing a 3D printing slurry according to claim 10, characterized in that: The organic monomer is one or more of isobornyl methacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, cyclic trimethylolpropane formal acrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate, tricyclodecane dimethanol diacrylate, hydroxyethyl methacrylate, and di-trimethylolpropane tetraacrylate.

15. The method for preparing a 3D printing slurry according to claim 10, characterized in that: The photoinitiator is one or more of camphorquinone and tertiary amine auxiliary initiator, bis(1-(2,4-difluorophenyl)-3-pyrrolyl)titanocene, N-alkylthioacridone, phenylethynyl dinitrophenol, 2,2-bis(o-chlorophenyl)-4,4,5,5-tetraphenyl-1,1-bisimidazole, 2,2,4-tris(2-chlorophenyl)-5-(3,4-dimethoxyphenyl)4,5-diphenyl-1,1-bisimidazole, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzoin diethyl ether, 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyl oxime).

16. The method for preparing a 3D printing slurry according to claim 10, characterized in that: In step (1), the speed of the electric stirrer is 800-1400 r / min, and the stirring time is 6-10 h; in step (2), the ball milling speed is 600-1000 r / min, the ball milling time is 12-24 h, and the ball-to-material ratio is 1:5; in step (3), a vacuum degassing machine is used for degassing, the vacuum degree is 0.1 mbar, and the air pump flow rate is 20-40 m 3 / h, degassing time is 3~5h.

Citation Information

Patent Citations

  • Ceramic slurry for DLP (Digital Light Processing) additive manufacturing and preparation method thereof, and method for preparing finished product by adopting slurry

    CN109133917A

  • Modification method of ceramic powder and ceramic powder

    CN111170747A

  • Zirconia ceramic powder for photocuring 3D printing and preparation method thereof

    CN114455946A

  • 3D printing high-transmittance ceramic tooth and preparation method thereof

    CN116023135A

  • Zirconia ceramic slurry, preparation method and application thereof, 3D printing zirconia ceramic and application thereof

    CN118145989A